On welfare pluralism, social policy and the contribution of sociology: Revisiting Robert Pinker - Offer, John (Frontiers in Sociology, 2023)
On occasion it makes sound sense to undertake a retrospective review of a late colleague's contribution to his or her subject area. This applies to Robert Pinker, Professor of Social Administration at the London School of Economics, who died at the age of 89 in February 2021. Over a long life he made a major impact on working for press freedom and to social work studies, but this article concerns his work on social policy, and particularly on the idea of welfare pluralism, a many-faceted idea the exploration of which powered two pathbreaking books Social Theory and Social Policy (1971) and The Idea of Welfare (1979). In the twentieth century many states including the United Kingdom had greatly expanded their welfare provisions for their citizens, and, in some, an academic subject area, often called social administration or social policy had grown in response. Pinker started writing in the 1960s, dissatisfied with the conventional approach of Richard Titmuss and others, almost exclusively concerned with the state and welfare. He made the case for a radical rebalance toward including everyday experiences of obligations and how familial informal welfare practices are strengthened, weakened or modified by formal social services. However, ahead of his time, Pinker was arguing for an enhanced sociological imagination in the study of social policy and on the very idea of “welfare”. This article has sections reflecting the facets of Pinker's thinking about welfare pluralism, including “social policy's past”, “exchange and stigma”, “taking informal welfare seriously”, “divergent views of altruism”, “comparative studies”, “on a mixture of means to welfare” and “aspects of Pinker's legacy”. The idea of welfare pluralism is now familiar. But Pinker's crucial pioneering role, depth of understanding of the issues and grasp of their intertwining is seldom recalled. This article should help to meet the need for his contribution to be reinserted into the mainstream of sociological thought on welfare, so enriching new research.